Clinical characteristics and genetic mutation analysis in 18 pediatric patients with Shwachman-Diamond syndrome - Wei, Ruoying; Zhang, Kaihui; Liu, Chen; Wei, Xuxia; Jiang, Qin; Li, Ji-an; Huo, Meiling; Liu, Yinggang; Abdalla, Mohnad; Du, Li-an; Yang, Xiaomei; Li, Fu (Frontiers in Genetics, 2025)
PurposeTo investigate the clinical features and genetic mutation spectrum of 18 children with Shwachman-Diamond syndrome (SDS).MethodsData from 18 children with SDS at Shandong University Affiliated Children’s Hospital (Ji’nan Children’s Hospital) between April 2016 and June 2024 were retrospectively analyzed. Variant sites were confirmed by Sanger sequencing in family lines.ResultsPatients exhibited complex and diverse clinical symptoms, often involving multiple systems. The clinical features of this cohort included (1) early onset (median age: 1.5 months), diarrhea, trypsin reduction, neutropenia, and growth retardation and (2) high incidence of pancreatic imaging abnormalities, bone marrow hypoplasia, developmental malformations, and neurocognitive disorders. All patients had homozygous or compound heterozygous SBDS mutations, with 258+2T>C identified as the hotspot mutation (20/37), while 41A>T and 185A>C were newly discovered mutations.ConclusionPatients with SDS exhibit clinical heterogeneity, and this study enriches the SBDS gene mutation spectrum. Genetic testing is valuable for early diagnosis.